2007
DOI: 10.1177/0020764006074292
|View full text |Cite
|
Sign up to set email alerts
|

A Clients' Perspective on Demand-Oriented and Demand-Driven Health Care

Abstract: Most clients in ambulatory mental health care appreciate the demand-oriented and demand-driven approaches. However, not all the elements are appreciated in the same manner. In general, clients do not seem to care much about who makes the decisions, but they care much more about the way the decision-making process is carried out. Clients especially value being heard and being involved in the process as a serious party.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Clients value being involved in the care process, being taken seriously and being consulted in the determination of their needs for care and services [48] with respect to their goals and preferences. As such, an organisation providing HWC services should arrange its care and service processes in such a way that they explicitly and adequately cater to the needs and requirements of elderly clients [68].…”
Section: Conversion To Daily Practice: Implications For Providersmentioning
confidence: 99%
“…Clients value being involved in the care process, being taken seriously and being consulted in the determination of their needs for care and services [48] with respect to their goals and preferences. As such, an organisation providing HWC services should arrange its care and service processes in such a way that they explicitly and adequately cater to the needs and requirements of elderly clients [68].…”
Section: Conversion To Daily Practice: Implications For Providersmentioning
confidence: 99%
“…However, although numerous studies have shown that clients support the core values of demand‐driven care, many authors point that clients are a heterogeneous group with different views about and different preferences for participation . Client characteristics that are known to affect participation in health care include age, gender, education, occupation and severity of disease .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, client satisfaction with services has been consistently associated with improved follow-up and adherence to treatment, as well as positive relationships with service providers (Hser et al 2004, Melnick et al 2004, Carlin et al 2005, Greenwood et al 2005, Brochu et al 2006, Rickmans et al 2007, Schulte et al 2007, 2011, Slote-Morris & McKeganey 2007.…”
Section: Introductionmentioning
confidence: 99%